2008
DOI: 10.1002/glia.20773
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces migration and invasion of glioma cells through MMP‐13 production

Abstract: Leptin, the product of the obses gene, plays an important role in the regulation of body weight by coordinating metabolism, feeding behavior, energy balance and neuroendocrine responses. However, central regulation of leptin gene expression is different from that in the adipocytes. In addition, leptin has been found in many tumor cell lines and has been shown to have mitogenic and angiogenic activity in a number of cell types. Glioma is the most common primary adult brain tumor with poor prognosis due to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 47 publications
3
64
1
1
Order By: Relevance
“…Furthermore, we demonstrated for the first time that leptin activates migration in human GBM cells, which is consistent with the observation that the hormone induces migration of rat C6 glioma cells (22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we demonstrated for the first time that leptin activates migration in human GBM cells, which is consistent with the observation that the hormone induces migration of rat C6 glioma cells (22).…”
Section: Discussionsupporting
confidence: 91%
“…Leptin is a recognized motogenic and angiogenic factor in cancer models (21) and induces migration in rat glioma cells (22); however, its role in human GBM migration has never been studied. We found that in LN229 and LN18 cells, leptin increased cell migration by ~50% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are a family of zinc-dependent endopeptidases with 24 identified members (42). There are reports showing that C6 cells express MMP-2, -9, -13, and membrane-type1 MMP (43,44). GM6001 inhibits MMP-1, -2, -3, -8, and -9 (45).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that C6 cells are a good tool for examining the underlying molecular machinery of clock gene expression because several clock genes are expressed and show the circadian oscillation after exposure to dexamethasone in these cells (20). In addition, we and another laboratory have examined various functions of astrocytes by using C6 cells (19,27). Therefore, although further investigation using by a primary culture of SCN astrocytes is necessary, it is possible that the characteristics of C6 cells might reflect in the SCN astrocytes.…”
Section: Discussionmentioning
confidence: 99%